Prader-Willi Syndrome: Clinical Aspects - Grechi Elena; Cammarata Bruna; Mariani Benedetta; Di Candia Stefania; Chiumello Giuseppe (Journal of Obesity)
Prader-Willi Syndrome (PWS) is a complex multisystem genetic disorder that shows great variability, with changing clinical features during a patient’s life. The syndrome is due to the loss of expression of several genes encoded on the proximal long arm of chromosome 15 (15q11.2–q13). The complex phenotype is most probably caused by a hypothalamic dysfunction that is responsible for hormonal dysfunctions and for absence of the sense of satiety. For this reason a Prader-Willi (PW) child develops hyperphagia during the initial stage of infancy that can lead to obesity and its complications. During infancy many PW child display a range of behavioural problems that become more noticeable in adolescence and adulthood and interfere mostly with quality of life. Early diagnosis of PWS is important for effective long-term management, and a precocious multidisciplinary approach is fundamental to improve quality of life, prevent complications, and prolong life expectancy.